SHIP RESISTANCE ANALYSIS WATERJET REMOTELY OPERATED VEHICLE (ROV) USING COMPUTATIONAL FLUID DYNAMICS (CFD) METHOD - Kause, Eurico Leonardo; Susanto, Tri (Department of Marine Engineering, Universitas Hang Tuah, 2025)
The propulsion system is a system that supports the performance of high-speed ships. Waterjet ship propulsion systems have long been known and used as propulsion systems for various types of ships, but their widespread application is still subject to their relatively low propulsive efficiency when compared to ship propulsion systems that use propellers, especially during relatively low ship speeds. The usual problem with ROVs using conventional propellers when inspecting in low water in the river is the blockage of river impurities, such as water hyacinths and underwater roots, on the ROV propellers. But there is a limitation to the problem when this waterjet is installed on the ROV should be used on inspections that do not work on the seabed, and the ROV can only be in a hovering position because the waterjet is susceptible to dirt. The purpose of this study was to analyze the ship's resistance of the waterjet remotely operated vehicle (ROV) propulsion system with the results of simulating the effect of the Waterjet ROV design on the total resistance of the Waterjet ROV increased by 5.69 N using the CFD method and the difference in prisoner comparison using the maxsurf method was 1.75%. The thrust analysis of the ROV model with a waterjet propulsion system has a higher thrust increase of 9.21 N when compared to the ROV model with a conventional propeller propulsion system, with a thrust value of 6.94 N. From the analysis of the fluid velocity contour results of the two best ROV models, namely the Waterjet ROV because the placement of the waterjet position on the outer side of the ROV frame so that the placement of the original Propeller inside the inner frame of the ROV is released as a result it tends not to create more turbulence and friction in the water in the middle of the ROV but the surface of the ROV frame on the outside which is added waterjet propulsion components causes higher hydrodynamic pressure.